Effect of Ti content on ablation behavior and mechanism of C/C-(Zr,Hf,Ti)C composites under oxyacetylene flame above 2600 °C - Junwen Liu; Yalei Wang; Zhiwei Qiao; Xiang Xiong; Ziwei Wang; Zhiyong Ye; Yanbin Wei (Journal of Materials Research and Technology, 2025)
C/C-(Zr,Hf,Ti)C composites were prepared via reactive melt infiltration adopting Zr-Hf-Ti mixed powder with different content of Ti (0 at%, 10 at%, 20 at% and 30 at%) as infiltrant. The influence of titanium content on the microstructure and ablation resistance of the composites was investigated after exposing to oxyacetylene flame at temperatures exceeding 2600 °C. Results showed that the most suitable content of Ti was 20 at%. This composition exhibited optimal ablation resistance, demonstrating a linear ablation rate of 3.5 μm/s and mass ablation rate of 1.5 mg/s. Compared with C/C-(Zr,Hf)C composites (0 at% Ti), these values were reduced by 53 % and 84 % respectively, which can be attributed to the formation of a dense (Zr,Hf,Ti)O2 protective oxide layer that effectively protected the underlying (Zr,Hf,Ti)C layer.